SPECIAL SYSTEM SECURITY INFORMATION OF LOCAL AREA NETWORK SOFTWARE - Литвинов, В. В.; Хоменко, А. В.; Дмитраш, О. В. (Science-based technologies, 2009)
In the given work there are the presented basic lines of the special local area network (CROW—BAR)software (SPZ), intended for prevention of unauthorized division of users CROW-BAR to the protected resources of the work stations (WS), servers of the common setting (SCS )and servers of management by defence (SMD), namely: copyprotected disks CD, SPZ and SMD, register of OS WS, SZP and SCZ, processes, that are executed on WS, SPZ, SMD.